2019
DOI: 10.1088/1361-648x/ab46d9
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of Majorana mode into correlated quantum dot nearby its singlet-doublet crossover

Abstract: We study quasiparticle spectrum of the correlated quantum dot deposited on superconducting substrate which is side-coupled to the Rashba nanochain, hosting Majorana end modes. Ground state of an isolated quantum dot proximitized to superconducting reservoirs is represented either by the singly occupied site or BCS-type superposition of the empty and doubly occupied configurations. Quantum phase transition between these distinct ground states is spectroscopically manifested by the in-gap Andreev states which cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…It is worth mentioning that Eq. ( 7 ) has the shape similar to those derived by Zienkiewicz et al 61 , Górski and Kucab 77 (without the S reservoir) and Ramos–Andrade et al 93 (for a QD between N leads and side coupled to two TSC nanowires). However, in none of these references finite , necessary for the estimation of the degree of Majorana nonlocality, was introduced.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…It is worth mentioning that Eq. ( 7 ) has the shape similar to those derived by Zienkiewicz et al 61 , Górski and Kucab 77 (without the S reservoir) and Ramos–Andrade et al 93 (for a QD between N leads and side coupled to two TSC nanowires). However, in none of these references finite , necessary for the estimation of the degree of Majorana nonlocality, was introduced.…”
Section: Methodssupporting
confidence: 81%
“…One can clearly notice the presence of the pronounced four peak structure around corresponding to the well resolved Andreev levels, appearing due to the QD-TSC coupling and splitted by the external magnetic field. Moreover, there is a visible zero-bias structure present because of the leakage of an isolated MBSs into the QD 18 , 58 , 61 , 65 , whose amplitude changes with , and reaches the maximal value of for .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical study of this behavior showed, that the interplay between trivial ABS and topological MBS strongly depends by spin polarization of the ABS [27,55,60,61], due to positive spin polarization of the MBS [28]. In such case, the avoided crossing or resonance of the ABS energy levels can be observed [62][63][64]. Moreover, this behavior can be helpful in distinguishing MBS from ABS [65,66].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Another important aspect making such hybrid systems interesting is related to the impact and signatures of the presence of Majorana modes in the transport properties of attached low-dimensional structures [13,[23][24][25][26][27][28][29][30][31][32][33][34]. In this regard, the leakage of Majorana zero-energy modes into attached quantum dots has been a subject of extensive investigations [35][36][37][38]. It was shown that the coupling to topological superconductor hosting Majorana quasiparticles (Majorana wire) results in fractional values of the conductance [35,39].…”
Section: Introductionmentioning
confidence: 99%